FOSTERING STUDENTS’ WRITING ACHIEVEMENT THROUGH WEBLOG - YUNANI ATMANEGARA; IRA IRZAWATI (Sriwijaya University Learning and Education International Conference, 2016)
To support students’ academic success, it is essential to equip them with good ability in writing. However, most of students encounter some problems in writing since writing involves essential, constructive, and complicated process. There are several ways to facilitate students to develop their writing. Due to many students inherent interest in technological things, thus implementing an online tool can be an alternative way to foster students’ writing achievement. One of the choices is using weblog. As many studies revealed that weblog could enhance students’ writing skills. Therefore, this study integrated weblog into students learning activities. Furthermore, it involved forty eleventh grade students that divided into two groups; experimental and control groups. At the end of the study, the students in experimental group gained better writing achievement than those who were in control group. It points out that learning through weblog could help students to enhance their writing achievement.